Prognostic value of vitamin-D level in non-metastatic breast cancer patients in Saudi Arabia. - Elsamany, Shereef; Elemam, Omaima; Zeeneldin, Ahmed; Elmorsy, Soha; Khatry, Ahmed; Alhuthali, Faisal; Alsayed, suha (Asian Pacific Journal of Cancer Care, 2020)
Background: Deficiency of vitamin-D (Vit-D) was associated with poor survival outcome in several studies across different tumour types. The present study aims to assess the prevalence and prognostic value of Vit-D deficiency among breast cancer patients in a single institution in Saudi Arabia. Methods: In this retrospective study, we screened patients who presented with non-metastatic breast cancer to King Abdullah Medical City, Saudi Arabia from June 2011 to December 2015. We checked baseline Vit-D level before starting systemic therapy in addition to other clinicopathological factors. Low Vit-D was defined as Vit-D level less than 30 ng /ml. The relations of Vit-D level (taking the median as the cutoff) with clinicopathological factors were assessed using Chi-Square test. Differences in survival outcome were compared using log rank test. Results: We screened 340 patients with non-metastatic breast cancer. Baseline Vit-D levels were available for 189 patients. The median age was 50 years (range: 26- 86 years). Noteworthy, 169 (89.4%) of patients had Vit-D level <30 ng/ml with a median of 14.9 ng/ml (range: 4.0 - 45.0). Low Vit-D level (below the median) was significantly more common in premenopausal (p=0.011) and ER-negative patients (p=0.011). However, lymphovascular invasion (p=0.001), clinically (p=0.023) and pathologically positive axillary LNs (p=0.041) were linked with higher Vit- D level. After a median follow up period of 58.2 months, 14 patients died and 40 relapsed. The 5-year disease-free survival (DFS) rates was 74.8%. The 5-year DFS rate in patients with higher Vit-D level above the median was 78.8% compared to 71.1% in patients with lower Vit-D level with no statistically significance difference (p= 0.22). The 5-year overall survival (OS) rate was 90.2%. Meanwhile, no difference in 5-year OS rate in patients with higher and lower Vit-D levels (90.3% and 89.7% respectively, p=0.6). Conclusion: Low Vit-D level was prevalent among the studied breast cancer patients. Low Vit-D level was associated with ER-negative phenotype and premenopausal patients. Baseline Vit-D level was not significantly linked with survival outcome.